Implementation of Digital Marketing SWOT Analysis on TikTok Shop Social Commerce: Implementasi Analisis SWOT Digital Marketing Pada Sosial Commerce TikTok Shop - Yusak, Zeindidia; Susyanti, Jeni; Asiyah, Siti (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
This study aims to analyze the application of SWOT analysis on TikTok Shop social commerce. This study used qualitative descriptive method. This method is an analysis method by providing a qualitative description of Strenghts, weaknesses, opportunities and threats in Social Commerce Tiktok Shop and SWOT analysis.    The results showed that in the SWOT analysis on TikTok Shop social commerce in the SWOT matrix, there are several strategies, including S-O, W-O, S-T and W-T that can be considered in making decisions in competing with other industries